Imperialisms in the olympics of the colonization in the postcolonization: Africa into the international olympic committee, 1910–1965 - (:unkn) unknown (My University, 2015)
After World War II, the principle of a colonized countries' self-determination was at stake in the international relationships emerging from the context of a Cold War and the decolonizations of Empires. Non-Governmental Organizations such as the International Olympic Committee (IOC) become not only analyzers of the effects of competition between the different colonial powers, but also enlighteners of the imperial strategies which would turn the power struggles into partnership and cooperation. The fear of a political harnessing from the Occidental countries resulted in two reactions: the progressive integration of English-speaking African National Olympic Committees (NOCs) based on a Great Britain-controlled International Federations (1950–1972) and, eventually and as a direct consequence, the creation of French-speaking African NOCs (1956–1968) through the International Olympic Aid Commission (1961). From 1944 to 1963, conditions for possibility seemed to be gathered for the realization of a process of internationalization of African sport through the integration of new English- and French-speaking African countries into the IOC.
Keywords: African Research